2010
DOI: 10.1128/jcm.02130-09
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Detection of Noroviruses and Sapoviruses in Swine and High Genetic Diversity of Porcine Sapovirus in Japan during Fiscal Year 2008

Abstract: A molecular biological survey on porcine norovirus (NoV) and sapovirus (SaV) was conducted in Toyama Prefecture, Japan, during fiscal year 2008. Both NoV and SaV were detected from swine fecal samples throughout the surveillance period, indicating that these viruses were circulating in this region. NoV strains detected in this study belonged to three genotypes that are known as typical swine NoVs. Although human NoVs were occasionally detected, it was unclear whether they replicated in pigs. As for SaV, genogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
62
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 57 publications
(87 reference statements)
3
62
0
3
Order By: Relevance
“…These differences could be due to different geographical locations, different ages of pigs sampled, or the use of different detection methods and primers with various specificities. Most porcine NoVs belong to the typical porcine genotypes (GII.11, -18, and -19), but human GII NoV-like RNA (GII.2, -3, -4, and -13) was occasionally detected from pigs in Asia (8,15). Overall there was no significant prevalence difference among the disinfection treatments (biocides and water control; see Table S1 in the supplemental material).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…These differences could be due to different geographical locations, different ages of pigs sampled, or the use of different detection methods and primers with various specificities. Most porcine NoVs belong to the typical porcine genotypes (GII.11, -18, and -19), but human GII NoV-like RNA (GII.2, -3, -4, and -13) was occasionally detected from pigs in Asia (8,15). Overall there was no significant prevalence difference among the disinfection treatments (biocides and water control; see Table S1 in the supplemental material).…”
Section: Discussionmentioning
confidence: 85%
“…Even though different ages of pigs were tested, NoVs were detected only in finisher pigs (7). A Canadian study reported 25% prevalence (41), and many other studies found lower prevalence rates: 2% to 4.6% in Europe (5, 42), 9% in New Zealand (43), 8% in Brazil (44), and Ͻ1% to 15% in Asia (8,15,22). These differences could be due to different geographical locations, different ages of pigs sampled, or the use of different detection methods and primers with various specificities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, human NoVs can replicate in gnotobiotic pigs, which indicates the possibility of the emergence of swine-human recombinant NoVs or that swine could serve as reservoir for human NoVs. Recently, the detection of human G2.3, G2.4, and G2.13 NoVs that were associated with human outbreaks in the same year was reported in swine in Japan (10). However, the low copy numbers of these viruses compared to swine NoV strains raises questions about whether the human NoVs replicated in the pigs or were the result of environmental contamination.…”
mentioning
confidence: 97%